2018
DOI: 10.3168/jds.2017-13823
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic, fermentation characterization, and resistance mechanism analysis of bacteriophage-resistant mutants of Lactobacillus delbrueckii ssp. bulgaricus isolated from traditional Chinese dairy products

Abstract: Bacteriophage infection is a large factor in dairy industrial production failure on the basis of pure inoculation fermentation, and developing good commercial starter cultures from wild dairy products and improving the environmental vigor of starter cultures by enhancing their phage resistance are still the most effective solutions. Here we used a spontaneous isolation method to obtain bacteriophage-resistant mutants of Lactobacillus delbrueckii ssp. bulgaricus strains that are used in traditional Chinese ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Having an A‐layer anchored on the LPS did not seem to modify the gel migration pattern (Shaw et al , ). A BIM may lose its ability to resist a phage if it is no longer exposed to it, or if the bacterium is subcultured several times (Deng et al , ). As previously noted (Imbault et al , ), BIMs generated from the A‐layer positive strain did not retain the resistance phenotype over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having an A‐layer anchored on the LPS did not seem to modify the gel migration pattern (Shaw et al , ). A BIM may lose its ability to resist a phage if it is no longer exposed to it, or if the bacterium is subcultured several times (Deng et al , ). As previously noted (Imbault et al , ), BIMs generated from the A‐layer positive strain did not retain the resistance phenotype over time.…”
Section: Discussionmentioning
confidence: 99%
“…In Lactobacillus delbrueckii subsp. bulgaricus , analysis of BIMs showed that the attachment and the adsorption of the phage to the bacterial receptor was a critical step, and that it was hindered by a change in the polysaccharide structure on their S‐layer (Deng et al , ). Other studies pointed to the presence of quorum‐sensing‐regulated phage defense mechanisms or changes in the gene sequence of the receptor (Hossain et al , ; Tan et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, after 10 h of infection, resistance was observed despite vB_EcoM-ECP26 being a lytic phage. This phenomenon might be due to the emergence of bacteriophage insensitive mutants (BIMs) by methods such as the restriction-modification system or CRISPR-Cas immunity [15,39]. BIM also can induced by altering the LPS or cell envelope structures [41].…”
Section: Growth Inhibition Assaymentioning
confidence: 99%
“…The differential phage susceptibility determinants are exchangeable between strains of a given species. Bacteria can gain or lose sensitivity to a given phage or the ability to support this phage development by mutation-, recombination-, or horizontal gene transfer-driven changes in their phage susceptibility or phage defence determinants [ 151 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 ]. Several genes associated with phage resistance or susceptibility are carried by mobile genetic elements [ 120 , 158 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 ].…”
Section: Future Possibilities To Produce Industrial Phage Propagamentioning
confidence: 99%